IS HBA1C A TRUE MARKER OF GLYCAEMIC CONTROL IN DIABETIC PATIENTS ON HAEMODIALYSIS? - Sayed, Mehwish; Adnan, Farzana; Majeed, Muneeba (Journal of Ayub Medical College Abbottabad, 2018)
Background: HbA1c is generally conducted to check blood glucose control in diabetic patients. As reported by several recent studies, HbA1c may not be considered as a reliable assay for monitoring glycaemic status in haemodialysis patients. Multiple factors may result in artificially low HbA1c. We sought to confirm this observation by performing a study in which we saw the agreement between expected HbA1c values as indicated by the mean plasma glucose level and the measured HbA1c values of haemodialysis dependent Diabetic patients. Methods: This cross-sectional study was conducted on 45 patients. Daily three readings of capillary blood glucose were taken for three consecutive days in a week, every two weeks in a month for up to three months. Total 54 capillary blood glucose levels were checked in the duration of three months. Mean blood glucose level was calculated at the end of the study and it is used to calculate the '˜expected HbA1c' levels using a formula. At the offset, HbA1c was measured (at 12 weeks) and was compared with the expected HbA1c. Results: On comparing the expected and measured HbA1c levels in 45 patients on haemodialysis. There is a significant difference between the two levels, with reduced levels of measured HbA1c in majority of patients as compared to expected ones. Conclusion: HbA1c is not a true marker of glucose control in diabetic patients on regular haemodialysis. Keywords: HbA1c; Haemodialysis; glycaemic control; capillary blood glucose; Diabetes Mellitus